Minorities in The Post-Soviet Space Thirty Years After the Dissolution of the USSR - Bocale, Paola (Quaderni del CERM, 2022)
When the Soviet Union broke apart in 1991, the Russian Federation and the newly independent republics of the Baltics, the Caucasus and Central Asia engaged in redefining their national identity in a challenging regional and global context. The stances and policies towards the minorities living in these countries became part of the striving towards national independence and identity formation. Despite vastly different post-Soviet nation-building trajectories, the development and implementation of state policies towards minorities had similar relevance and importance across the region. Thirty years after the end of the USSR what is the situation of minorities and minority issues in the countries that emerged from that multi-ethnic state? How have the former republics - including Russia dealt with their minorities and minority affairs? To what protection and rights are minority communities entitled to? Studies of the dissolution of the USSR and of nation-building in the independent post-Soviet states have flourished over the past decades. However, despite the relevance of the theme, there is a dearth of specialist publications which address the many issues related to minority communities in the post-Soviet space. This volume attempts to fill this gap by providing a collection of essays covering some of the most relevant aspects of the contemporary status and situation of minorities in the area.